Detection of Pathogenic Escherichia coli in Duck Intestine Slaughtered at Lambaro Market Aceh Besar - Erina, Erina; Panjaitan, Tasya Adilla; AK, M. Daud; Sari, Wahyu Eka; Rusli, Rusli; Helmi, Teuku Zahrial (Jurnal Medika Veterinaria, 2025)
Pathogenic Escherichia coli is a type of bacteria that has the ability to cause disease in hosts, including humans and animals, although in general E. coli acts as a normal flora in the digestive tract. This study aimed to detect the presence of pathogenic E. coli in the intestines of ducks sold at Lambaro Market, Aceh Besar. E. coli is a normal flora bacteria in the digestive tract of animals and humans, but some strains are pathogenic and can cause zoonotic diseases. The presence of pathogenic E. coli in poultry products has the potential to be a source of infection for humans through consumption of contaminated food. This study used 15 duck intestine samples obtained from cecum, to identify the presence of pathogenic E.coli. The results showed that 13 samples produced clear colonies on Sorbitol MacConky Agar (SMAC), indicating the inability of bacteria to ferment sorbitol, which correlated to the presence of pathogenic E. coli. In contrast, two samples showed pink colonies indicating the presence of nonpathogenic E. coli. The conclusion of this study was the cecum of ducks sold at Lambaro Market, Aceh Besar positive for pathogenic E. coli.